2017
DOI: 10.1111/rda.12969
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mesenchymal stem cells in bovine endometrium during follicular phase of oestrous cycle

Abstract: Stem cells have been postulated as responsible for cell regeneration in highly and continuously regenerative tissues such as the endometrium. Few studies in cattle have identified and specified the presence of stem cells in the endometrium during the oestrous cycle. The aim of this study was to investigate the presence of mesenchymal stem cells (MSCs) in the bovine endometrium during the follicular phase (FP) of the oestrous cycle. Uterine tissue was collected in the time-frame comprising day 18 of the cycle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…Previously, our group has reported similar cells in cyclic cows [ 19 , 20 ]; therefore, it was not unexpected to identify equivalent cell populations in puerperal healthy endometrium. To a similar extent, cells displaying the same properties were identified in this study in cows with subclinical endometritis, and CE and CDT were not different from healthy cows.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previously, our group has reported similar cells in cyclic cows [ 19 , 20 ]; therefore, it was not unexpected to identify equivalent cell populations in puerperal healthy endometrium. To a similar extent, cells displaying the same properties were identified in this study in cows with subclinical endometritis, and CE and CDT were not different from healthy cows.…”
Section: Discussionmentioning
confidence: 66%
“…MSCs are present in the endometrium of several species including humans, mice, pigs, and ruminants [ 14 18 ]. Our group was able to isolate and characterize these cells in cattle endometrium for the first time throughout all the stages of the estrus cycle in healthy bovine endometrium [ 19 , 20 ]. Taking into consideration the crucial role of PGE 2 in endometritis-mediated inflammation as well as in MSC rescue as described earlier and the presence of MSCs in the endometrium of healthy cows, we postulated the hypothesis that pathological inflammation of the uterus as in endometritis affects the presence and functionality of such endometrial MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…We report here the identification of stromal and perivascular cells that expressed mesenchymal stem cell markers in the porcine endometrium. Recent studies on bovine endometrium have shown that candidate MSCs are confined to glandular and stromal cells expressing Oct4 and Sox2 in their nuclear and perinuclear regions and CD44 at the cell membrane (Cabezas et al., ; Lara et al., ). Another report has found that the side‐population cells immunoreactive for ABCB1 (ATP‐binding cassette, sub‐family B member 1) transporter reside between the stromal and epithelial layers in porcine endometrium (Bodek et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, alternative mammalian models have been developed to define endometrial stem/progenitor cells, namely porcine (Bodek, Bukowska, Wisniewska, & Ziecik, ; Bukowska, Ziecik, Laguna, Gawronska‐Kozak, & Bodek, ; Miernik & Karasinski, ; Subbarao et al., ), bovine (Cabezas et al., ; Donofrio, Franceschi, Capocefalo, Cavirani, & Sheldon, ; Lara, Rivera, Rojas, Rodríguez‐Alvarez, & Castro, ; Łupicka, Bodek, Shpigel, Elnekave, & Korzekwa, ; de Moraes et al., ), ovine (Letouzey et al., ), canine (De Cesaris et al., ) and equine (Rink et al., ). Among them, pigs have become increasingly valuable as a model for translational research due to many genetic, anatomical and physiological similarities to human (Gonçalves, Ambrósio, & Piedrahita, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation